The Influence of Customer Orientation on Customer Relationship in Telecom Services - Junaid-ul-haq, Junaid-ul-haq; ., Saqib Mehmood (Information Management and Business Review, 2011)
In this study, an effort has been made to disclose the influence of customer orientation on customer retention. It has also revealed that customer orientation influences on customer satisfaction and customer trust and their ultimate effect on customer Retention. Primary data was collected through questionnaire survey.290 questionnaires were distributed out of which 219 were received and supposed for analysis purpose, 75.51% which is considered as a serious response rate of our respondents. Customer orientation has positive effect on customer satisfaction as well as on customer trust, which shows significant relationship of customer orientation on customer satisfaction and customer trust. Moreover, satisfaction and trust of customer has effect on customer retention. Satisfaction of customer has negative effect due to one or more reason, whereas, customer trust has positive and significant effect on customer retention. Customer orientated organizations earn more profit and can control customer retention. Findings of this study can also be used to control the customer retention. While customer orientation is under discussion then it has two major factors i.e. customer satisfaction and customer trust, organizations should more focus on these factors. Sometime when customer retention takes place even focusing these factors then current competitor’s strategies can also be kept in mind. This study is done in a developing country where there is a very tough competition among service providers to enhance their market share. The focus of this research is to control the switching customer, which is the one of the important problems facing by the service providers.